2013
DOI: 10.1097/01.jaa.0000431512.13196.f3
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum from a severe asthma attack

Abstract: Spontaneous pneumomediastinum is a rare complication of an asthma exacerbation characterized by chest pain, dyspnea, neck swelling, and subcutaneous emphysema. Although the condition is usually benign and treatment is primarily supportive, surgical intervention may be needed if the patient develops hemodynamic or respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Other studies have found the incidence to be much lower (one in 30,000). 10 The main treatment strategy employed for the patient's pneumomediastinum, pneumoretroperitoneum, and hypercapnic respiratory failure was lung protective ventilation. The patient's ventilator settings were continuously readjusted based on arterial blood gas findings that were performed daily and in response to changes in clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found the incidence to be much lower (one in 30,000). 10 The main treatment strategy employed for the patient's pneumomediastinum, pneumoretroperitoneum, and hypercapnic respiratory failure was lung protective ventilation. The patient's ventilator settings were continuously readjusted based on arterial blood gas findings that were performed daily and in response to changes in clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of SPM is reported to be 0.001–0.01% of all adult inpatients and is said to be more common in young males [ 1 ]. The causes of SPM are retching, vomiting, acute asthma attack, intense sport activity, inhalation of drugs, weight loss as seen in anorexia nervosa [ 2 , 3 ]. The inciting event in our case is probably the intense physical activity of lifting 100 coconut fronds.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous pneumomediastinum is rare in the paediatric population. Secondary spontaneous pneumomediastinum is often associated with a respiratory tract infection or an asthma exacerbation, as in this case 1–4. Clinical presentation includes more frequently chest pain and cough 3.…”
Section: Descriptionmentioning
confidence: 99%